1968
DOI: 10.1002/j.1537-2197.1968.tb07438.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsella Embryogenesis: The Egg, Zygote, and Young Embryo

Abstract: The ultrastructure and composition of the egg, zygote, and young embryo of Capsella bursa‐pastoris were examined. The egg is a highly polarized cell; one‐half to one‐third of the micropylar end is filled with a large vacuole while the chalazal end contains the nucleus and much of the cytoplasm of the cell. The wall which surrounds the cell is incomplete at the chalazal end. Ribosomes fill the cytoplasm and show little or no aggregation into polysomes. The structure of the nucleolus suggests that ribosomes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(39 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…Morphogenetic events for organ diVerentiation occur after the globular embryo stage, although Wxed and variant patterns of cell division during the development of zygotes into globular embryos have been reported depending on the species (Pollock and Jensen 1964;Schulz and Jensen 1968;Tykarska 1979;Schel et al 1984;. Recently, it was proposed that a globular embryo can be divided into domains, demarcated by gene expression patterns, with distinct developmental fates (Bowman and Eshed 2000;Laux et al 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Morphogenetic events for organ diVerentiation occur after the globular embryo stage, although Wxed and variant patterns of cell division during the development of zygotes into globular embryos have been reported depending on the species (Pollock and Jensen 1964;Schulz and Jensen 1968;Tykarska 1979;Schel et al 1984;. Recently, it was proposed that a globular embryo can be divided into domains, demarcated by gene expression patterns, with distinct developmental fates (Bowman and Eshed 2000;Laux et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Vacuoles in the zygote were less developed than those in the egg cell, and cytoplasmic density appeared to increase in the zygote after fertilization. Fertilization-induced cell elongation/enlargement was not observed in rice zygotes, although zygote elongation/ enlargement has been reported in some species; for example, Arabidopsis (MansWeld and Briarty 1991), Capsella bursa-pastoris (Schulz and Jensen 1968) and Cypripedium insigne (Poddubnaya-Arnoldi 1967). At 24 h after Xowering, an early embryo consisting of several cells was observed (Fig.…”
Section: Early Embryonic Development In Plantamentioning
confidence: 91%
“…The fact that the overall intercellular movement of the fluorescently labelled probes was enhanced rather that reduced in the TCLs could indicate that the reprogramming of a young vegetative internode into a sheet of vegetative adventitious shoots might not be so great a change in developmental fate that cell isolation is a requirement. At the same time, cell isolation observed during in vitro embryogenesis (Ehlers and Kollmann 2000) might reflect a need to keep embryonic tissue separate from the parent or adult tissue (Schulz and Jensen 1968) and be part of the programming of embryogenesis rather than a prerequisite for regeneration. Indeed, if the TCLs had been manipulated to regenerate floral shoots, roots or callus (Chlyah 1973; Tran Thanh Van et al 1974) then there might have been a different outcome characteristic of those tissue types.…”
Section: Symplastic Patterning Within Torenia Meristems and Shootsmentioning
confidence: 98%
“…These observations indicate that there is no universal pattern of early cell cleavage that describes embryonic development. Despite such variable embryogenesis patterns, it has been shown that zygotic cell division is asymmetric in most angiosperms and that the apical cell of the two-celled embryo develops into the embryo proper while the basal cell develops into the suspensor and hypophysis (Pritchard 1964;Schulz and Jensen 1968;Tykarska 1976;Schel et al 1984;reviewed in Lindsey and Topping 1993). In addition to cytological observations of asymmetric cleavage of plant zygotes, Haecker et al (2004) reported that two putative homeotic genes, WUSCHEL HOMEOBOX2 (WOX2) and WOX8, are specifically expressed in the apical and basal cells of the Arabidopsis two-celled embryo, respectively, suggesting that the two daughter cells from a zygote possess different transcriptional profiles.…”
Section: Introductionmentioning
confidence: 97%
“…The central cell fuses with the second sperm cell to form a triploid primary endosperm cell, which develops into the endosperm (Guignard 1899;Nawaschin 1898;Russell 1992). In some dicot plants, such as the crucifers Arabidopsis, Brassica napus and Capsella bursa-pastoris, the pattern of cell division during early embryogenesis is fixed, and the cell fate is traceable (Mansfield and Briarty 1991;Schulz and Jensen 1968;Tykarska 1979). On the other hand, in many plant species, for example cotton (Pollock and Jensen 1964) and grasses such as maize (Schel et al 1984), variant cell division occurs during embryogenesis.…”
Section: Introductionmentioning
confidence: 97%